Implementasi Undang-Undang Nomor 12 Tahun 2022 Tentang Tindak Pidana Kekerasan seksual (TPKS) Di Kota Pekanbaru: Peluang dan Tantangannya - Siti Fatimah; Mustiqowati Ummul Fithriyyah (JDKP Jurnal Desentralisasi dan Kebijakan Publik, 2023)
Sexual violence against children that occurs in the city of pekanbaru continues to increase every year. where this becomes an urgency for the pekanbaru city government to overcome the issue of the phenomenon. The Law on Sexual Violence is a law that was passed on April 12, 2022 through a very long journey starting from 2012 and the rejection of several parties until it was finally passed. With the passing of the TPKS Law, it is a form of protection provided by the government to prevent and provide security to the community, especially women and children who are vulnerable to sexual violence. the purpose of this study is to find out how the opportunities and challenges faced in the implementation of the Law on the Crime of Sexual Violence (TPKS). By using the theory of policy implementation by Daniel Mazmanian and Paul A Sobatie with 3 indicators. The results showed that the challenges faced in the implementation of this Law are: (1). The social, economic and technological conditions of the community are inadequate so that they affect the implementation of the implementation of Law No. 12 of 2022 concerning Criminal Acts of Sexual Violence. (2). public socialization, which is carried out by DP3APM is not fully maximized because it only uses social media as a forum in carrying out its duties as a place of prevention and guidance in terms of preventing sexual violence against children. Keywords: policy implementation, sexual violence, Law, TPKS